ROLE OF MINDFULNESS IN MENTAL HEALTH AND OVERUSES OF SMARTPHONEAMONG ADULTS - Ambica; Barmola, KC (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Overuse of Smartphone can lead to obsessive behavior and exacerbate mental health problems such as depression, anxiety, and stress. Mental health encompasses cognitive, behavioral, and emotional well-being. It has an impact on how we feel, think, and behave. It also determines how we handle stress, connect with others, and make decisions. Many people who suffer from mental health illnesses have many conditions. Mindfulness therapy alleviates mental health issues such as sadness, anxiety, and stress. Mindfulness-based therapies are increasingly being utilized to treat psychological problems, and they have been demonstrated to be beneficial in treating depression and preventing relapse. The current study examined relevant literature to better understand the role of mindfulness in dealing with Smartphone misuse, depression, anxiety, and stress. Finally, mindfulness intervention may assist to prevent mental health difficulties and Smartphone overuse among adults.